The Effect of Premium Service Music Streaming Towards Consumer Satisfaction of Z Generation in Jakarta - Airlangga Muhammad Syahraihan; Muhammad Aras; Diva Berlian Maahirah; Zahra Azizah Rizki; Michelle Lay (Jurnal Indonesia Sosial Teknologi, 2024)
The development of the internet and technology affects many aspects of life, such as the need to listen to music. To fulfill this need, new technology presents music streaming to make it easier for people to listen to music. Music streaming provides premium services to give users advantages when streaming music. The availability of premium service is expected to increase consumers’ satisfaction. This research aimed to identify premium service's effect on consumer satisfaction. This research used a quantitative method and a descriptive approach. This research sample was 100 Gen Z people in Jakarta, and music streaming was used. The data will be analyzed by using SPSS. The findings of this research showed the effect of premium service music streaming on consumer satisfaction of the Z generation with t value ≥ t table, and the result was 3.414 ≥ 1.664.